Comparison of Adipose Distribution Indices with Gold Standard Body Composition Assessments in the EMPA-REG H2H SU Trial: A Body Composition Sub-Study. Issue 4 (December 2015) - Neeland, Ian; McGuire, Darren; Eliasson, Björn; Ridderstråle, Martin; Zeller, Cordula; Woerle, Hans; Broedl, Uli; Johansen, Odd
Abstract Introduction Excess adiposity contributes to cardiometabolic disease. Although adipose depots can be measured using imaging, implementation remains limited in practice. Data comparing surrogate indices of total and visceral adiposity with gold standard measurements in the context of a clinical trial population are lacking. We explored the relationships between adipose distribution indices and imaging assessments of body composition using baseline data from the EMPA-REG H2H SU™ trial. Methods 118 participants from the Phase III trial of empagliflozin 25 mg vs. glimepiride 1–4 mg enrolled in a dedicated sub-study underwent assessment of total fat and fat-free mass by dual x-ray absorptiometry (n = 93) and abdominal visceral (VAT) and subcutaneous adipose tissue by magnetic resonance imaging (n = 99). Correlations with waist circumference (WC), estimated total body fat (eTBF), index of central obesity (ICO), and visceral adiposity index (VAI) were assessed. Results eTBF was highly representative of total body fat (Spearman'sρ = 0.73, P < 0.001) but not associated with VAT. WC and ICO were strongly, and VAI to a lesser degree, correlated with VAT (ρ = 0.66, P < 0.001;ρ = 0.52, P < 0.001;ρ = 0.24, P = 0.02, respectively). Conclusion These findings support the use of eTBF and WC or ICO as surrogate indices for total body fat and VAT, respectively, in the absence of gold standard imaging methodology.